DIDACTIC-DEMOCRATIC PARADIGM OF TEACHING CHOREOGRAPHY: THE UK EXPERIENCE (Comparative Professional Pedagogy, 2022)
The article is devoted to the disclosure of the didactic features of the choreographers’ professional training in UK experience. It is found out that British teachers take into account new theories of the synthesis of music and dance art, dance and digital pedagogy, choreography, and sports. The "didactic-democratic spectrum" of training is characterized as a new paradigm of teaching choreographic art, which is based on the socio-artistic relations between the choreographer and the performer (new roles of the choreographer and the performer: "expert - performer", "director – translator", "facilitator – creator", "co-author – co-performer", "artist – narrator", etc.) It is substantiated that the didactic component covers teaching choreography on the principle of "teaching by showing", and democratic component covers a learning process based on cooperation, and partner interaction ("collaborative dance learning"). It is established that the "didactic" concept refers not only to the educational element "learning through demonstration", but also to the development of learning skills; the "democratic" concept is reflected in the social character dance, shades of democratic equality in dance on the basis of partnership and tolerance. The mechanism of step-by-step implementation and the content of the didactic-democratic spectrum of teaching choreography are presented. The model promotes the strengthening of the relationship between theoretical and practical learning based on facilitation, independent expertise in choreography learning, democratic teaching style, taking into account personal experience of the student and teacher, reflection and self-regulation, principles of social interaction, a balanced approach to teaching choreography. It is established that the development of choreographic skills in various styles of dance in British didactics is guided by the theory of constructivism, which is interpreted into the pedagogical theory of "dance notation pedagogy", which, in combination with Bloom's taxonomy, helps to outline motives, desires, interests in professional activity in general and in relation to the chosen dance style. It is concluded that the British system of choreographic education is based on the principles of "author's schools", choreographic amateurism, freedom of choice, freedom of creativity and improvisation, social and dance leadership.
Keywords: professional training; Great Britain; didactic-democratic spectrum; choreographic art; choreographer; training; methodology